Perbandingan Konsumsi Buah Naga dan Sari Kacang Hijau terhadap Peningkatan Kadar Hb pada Ibu Hamil Anemia di Wilayah Puskesmas Mranggen II Kecamatan Mranggen Kabupaten Demak - Dewi Andang Prastika; Amanda Sasha Febiani; Budi Astyandini (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2023)
ABSTRACT Background: Anemia is still a complex health problem in Indonesian women. The most common cause of anemia in pregnancy is lack of nutrients in the body. Pharmacological treatment has side effects faster than non-pharmacological treatment. Natural products that are traditionally used as an additional intake in the prevention of anemia, for example there are dragon fruit, green beans, and so on. Purpose: The purpose of this study was to determine the effectiveness comparison between consumption of dragon fruit and mung bean juice on increasing Hb levels in anemia pregnant women in the Mranggen II Public Health Center, Demak Regency. This type of research is quantitative research with a research design using Two Group Pretest Posttest Design. The population in this study were pregnant women with anemia. Sampling using the entire population of as many as 40 respondents. Giving dragon fruit in the form of pieces shows 100% of the ingredients used and green beans are made by boiling to get the juice from the green beans. The research instrument was the Easy Touch Hb test as a measuring tool for Hb levels. Data analysis used Paired T-Test / T-dependent test. Result: The results showed that the average hemoglobin level of pregnant women with anemia in the intervention group before being given Dragon Fruit had a Mean value of 10.241 g/dl, while after the intervention the Mean value became 11.125 g/dl. The Hb level in the control group before being given Mung Bean Extract had a Mean value of 10.825 g/dl while after being given Mung Bean Extract the Mean value became 11.266 g/dl. The results of the statistical test using the Independent T-Test between the two intervention groups and the control group showed p-values 0.539 which means there is no difference in the effectiveness of giving Dragon Fruit and Green Bean Extract to increase Hb levels in pregnant women with anemia. Keywords: Dragon fruit, Green Beans, Increased Hb levels, pregnancy